Co‐expression networks of deacclimation‐impaired transcription factor mutants identified complex regulation of the cold stress release response. Issue 4 (25th August 2022) - Vyse, Kora; Fischer, Axel; Zajancauskaite, Greta; Erban, Alexander; Kopka, Joachim; Balazadeh, Salma; Zuther, Ellen
Abstract: Plants adapt to cold, non‐freezing temperatures through cold acclimation and lose acquired freezing tolerance in warmer temperatures in a process called deacclimation. This work identified a hypoxia response during early deacclimation evidenced by increased ADH activity and upregulated gene expression of hypoxia markers. Mutants defective in hypoxia response and transcription factors transiently induced during deacclimation, hra1, lbd41, mbf1c, and jub1, revealed slower deacclimation rates. Comparative transcriptome (RNA‐Seq) and co‐expression analysis of Col‐0, mbf1c, and jub1 pointed to an involvement of genes encoding thermoswitches, cell wall remodelers, ABC‐transporters, and H + ‐ATPases in regulating the deacclimation rate. In mbf1c and jub1, unique increases of stress‐responsive genes and genes involved in jasmonic acid regulation were detected and linked to freezing tolerance retention during deacclimation. Data of this study are in agreement with previous observations of hypoxic niches within the plants and connected effects on growth and development during deacclimation. Regulation of deacclimation was shown to be a complex process, finely tuned to achieve an optimal rate and onset of deacclimation in plants. Candidate genes for future targeted analyses of this regulation are also suggested.